Synthetic cannabinoid JWH-073 alters both acute behavior and in vivo/vitro electrophysiological responses in mice - Barbieri, Mario; Tirri, Micaela; Bilel, Sabrine; Arfè, Raffaella; Corli, Giorgia; Marchetti, Beatrice; Caruso, Lorenzo; Soukupova, Marie; Cristofori, Virginia; Serpelloni, Giovanni; Marti, Matteo (Frontiers in Psychiatry, 2022)
JWH-073 is a synthetic cannabinoid (SCB) receptor agonist illegally marketed within “herbal blend”, causing psychoactive effects more intense than those produced by Cannabis. However, consumers report that JWH-073 causes less harmful effects than those induced by other SCBs, misrepresenting it as “safe JWH-018 alternative”, which in turn prompts its recreational use. The present study is aimed at investigating the in vivo pharmacological activity of acute JWH-073 injection in male CD-1 mice at dosage underactive or ineffective on physiological and neurobehavioural parameters in mice. To this aim we investigate the effect of JWH-073 on sensorimotor (visual, acoustic and tactile), motor (spontaneous motor activity and catalepsy) and memory functions (novel object recognition; NOR) in mice coupling behavioral and EEG data. Moreover, to clarify how memory function is affected by JWH-073, we performed in vitro electrophysiological studies in hippocampal preparations using a Long-Term Potentiation (LTP) stimulation paradigm. The present study demonstrates that acute administration of a mild dose of JWH-073 (1 mg/kg i.p.) transiently impairs motor activity and visual sensorimotor responses up to 25 and 105 minutes respectively, while it alters for a longer time (up to 24 hours) the memory function in mice. Significant immediate alterations of delta and theta EEG bands in somatosensory cortex and hippocampus coupled with behavioral changes are observed. Moreover, in vitro results support cognitive function impairment by interfering with hippocampal synaptic transmission and LTP generation. Our results suggest that JWH-073, deeply alters brain electrical responsiveness with minor behavioral symptoms. Thus, it poses a subtle threat to consumers who mistakenly consider it as safer than other SCBs.